2022
DOI: 10.1108/ijopm-01-2022-0015
|View full text |Cite
|
Sign up to set email alerts
|

The roles of national culture in affecting quality management practices and quality performance - multilevel and multi-country analysis

Abstract: PurposeThis study investigates the role of national culture on the implementation and effectiveness of quality management practices. Specifically, the authors examine the dual roles of two of Hofstede's national culture dimensions (individualism and indulgence) in driving the implementation of people management practices and in moderating the relationship between people management and product quality performance.Design/methodology/approachThe authors’ dataset combines a survey of 976 firms from 22 countries wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Openness & Action Orientation). This focus has been a good choice of the institutions, because research has shown that when people get along better with each other in an organisation, that this forms the basis of successful change in that organisation [38,39]. Appendix 2 shows all three institutions have advanced on people being allowed to make mistakes (characteristic 12); being open to change (13); their managers being trusted (15), having integrity (16) and being a role model (17) and a coach to employees (20); and having a diverse workforce (29) in a secure environment (35).…”
Section: The Second Hpo Diagnosis (2022)mentioning
confidence: 99%
“…Openness & Action Orientation). This focus has been a good choice of the institutions, because research has shown that when people get along better with each other in an organisation, that this forms the basis of successful change in that organisation [38,39]. Appendix 2 shows all three institutions have advanced on people being allowed to make mistakes (characteristic 12); being open to change (13); their managers being trusted (15), having integrity (16) and being a role model (17) and a coach to employees (20); and having a diverse workforce (29) in a secure environment (35).…”
Section: The Second Hpo Diagnosis (2022)mentioning
confidence: 99%
“…In a study of 42 countries over a 20-year period, Thanetsunthorn [49] found that culture influenced trust in organisational development. Furthermore, research on 976 companies in 22 countries showed that culture influenced quality management and performance [50], whereas research on 191 international firms in 29 countries and five continents found that cultural factors can influence ethical issues [51]. In addition, socio-cultural factors can influence public investment [17], civil unrest [52], labour productivity [16], digitalisation [26], tax compliance [20] and high-tech innovation [25], among others.…”
Section: Socio-cultural Factors and The Digital Economymentioning
confidence: 99%
“…While the unit of analysis for cultural distance could range from individual-to national-level, the focus here is at the national level based on Hofstede's (1984) four dimensions of culture: power distance, uncertainty avoidance, individualism and masculinity (Kaufmann and Carter, 2006). Cultural distance influences the way managers communicate and implement practices, including quality management practices (Prajogo et al, 2022), approaches used when confronting new or challenging problems (Joynt and Warner, 1996), as well as relationships between firms (Gorodnichenko et al, 2023;Thornton et al, 2013). Cultural differences make it more challenging to transfer knowledge and align interests among supply chain members (Liu et al, 2021).…”
Section: Distance and Product Safety Consumer Protection Practicesmentioning
confidence: 99%